1999
DOI: 10.1159/000029430
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adhesion Molecule Profiles on Alveolar Macrophages and Blood Leukocytes

Abstract: Background: Cell adhesion molecules are believed to be essential for blood cell recruitment to the lung and for the movement of alveolar macrophages (AM) within the lung. Objective: To investigate the expression pattern of L-selectin and β2 integrins on blood leukocytes and AM, including AM of various maturity. Methods: Flow cytometry was used to study the expression of L-selectin (CD62L) and of the β2 integrins CD11a, CD11b, and CD11c on AM (including density-defined subpopulations), mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…Overexpression of CD11b/CD18 on leukocyte surfaces in ragpickers, therefore, possibly underscores stimulation of immune defense to combat pathogenic microorganisms in their working environment 16) . This is consistent with a report showing higher expression of CD11b on neutrophil and monocyte surfaces during challenge from bacterial pathogens 20) . Sustained overexpression of β 2 Mac-1 integrin, however, could be harmful because it prolongs inflammation by delaying neutrophil apoptosis causing tissue damage 6) .…”
Section: Discussionsupporting
confidence: 93%
“…Overexpression of CD11b/CD18 on leukocyte surfaces in ragpickers, therefore, possibly underscores stimulation of immune defense to combat pathogenic microorganisms in their working environment 16) . This is consistent with a report showing higher expression of CD11b on neutrophil and monocyte surfaces during challenge from bacterial pathogens 20) . Sustained overexpression of β 2 Mac-1 integrin, however, could be harmful because it prolongs inflammation by delaying neutrophil apoptosis causing tissue damage 6) .…”
Section: Discussionsupporting
confidence: 93%
“…S5), consistent with previous studies (23,24). The inclusion of anti-L-selectin antibody significantly (p Ͻ 0.05) reduced the binding of fluorescently labeled GdA to monocytes (Fig.…”
Section: Sialylation Of Gda Is Not Needed For Gda-induced Il-6supporting
confidence: 91%
“…In this study, we report that cells developed from cultured monocytes displayed the phenotype of tissue macrophages with the phenotype CD14 low CD11b low CD64 low HLA-DR + [24][25][26][27], and SB203580 and tyrphostin 25 did not alter the maturation process of monocytes. We recently showed that the inflammatory cytokines IFN-␥ and TGF-␤1, which accelerated differentiation of monocytes, down-regulated MMP-9 synthesis and release in differentiating cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…2). Indomethacin 25 29 ± 6 (2-13) 27 ± 9 (7-59) 48 ± 3 * (21-290) 12 ± 6 (46-90) +Both 28 ± 5 (14-17) 36 ± 11 67 SB202474 (5 M), an inactive analog of SB203580 for p38 MAPK inhibition study [30] was without effect (<10%, data not shown). When added together, tyrphostin 25 and SB203580 inhibited MMP-9 production (Fig.…”
Section: Sb203580 and Tyrphostin 25 Inhibit Mmp-9 Synthesis And Releamentioning
confidence: 93%
See 1 more Smart Citation